The Prevalence of Previous Coronavirus Disease-19 in Patients with Pulmonary Thromboembolism and Its Effect on Embolism Severity - Kocak, Nagihan Durmus; Tutar, Nuri; Cil, Gizem; Afsin, Emine; Senturk, Aysegul; Aydin, Derya; Pala, Ayse (Mdpi, 2025)
Background/Objectives: The association between past coronavirus disease-19 (COVID-19) infection and pulmonary thromboembolism (PTE) is a potential research topic. We aimed to research the prevalence of previous COVID-19 infection in patients with PTE and to determine whether there is a difference in embolism severity in these cases. Methods: Study design: Multicenter, observational, cross-sectional. Patients diagnosed with PTE between 11 March 2022 and 11 March 2023 were prospectively included in this study, excluding cases with PTE along with active COVID-19, patients under the age of 18, and pregnant patients. Group 1 consisted of PTE cases with previous COVID-19, and Group 2 consisted of PTE cases without previous COVID-19. Key variables are D-Dimer level, right ventricle/left ventricle (RV/LV) ratio, simplified pulmonary embolism severity score, and treatment type. Results: A total of 1185 patients (Group 1; n = 360, Group 2; n = 825) were included in this study. The proportion of patients with RV/LV ratio > 1 on computed tomography pulmonary angiography (CTPA) was significantly high in Group 2 compared to Group 1 (27.9% vs. 19.7%, p = 0.003). In multivariate logistic regression analysis, the absence of any identifiable risk factor for PTE was found to be a 0.46-fold protective factor in the presence of previous COVID-19 (OR: 0.456 95% CI: 0.274-0.760, Wald = 9.070, df = 1, p = 0.003) and an RV/LV ratio > 1 on CTPA was found to be a 0.60-fold protective factor (OR: 0.603, 95% CI: 0.365-0.998, Wald = 3.874, df = 1, p = 0.049). Conclusions: The prevalence of previous COVID-19 infection in PTE cases was 30.4%, and 26.3% of idiopathic cases had previous COVID-19 infection. Although the parameters related to embolism severity were higher in the non-COVID-19 group, multivariate analyses revealed a 2.2-fold increased risk for idiopathic PTE and a 1.7-fold increased risk for RV/LV ratio > 1 on CTPA in patients without COVID-19 compared to those with prior COVID-19.
Keywords: COVID-19; hospital mortality; patient acuity; pulmonary embolism; risk factors